Siapa yang Berkuasa Saat Krisis? Menelusuri Logika Epistokratik dalam Penanganan Pandemi COVID-19 di Indonesia - Reynaldi, Dwiki Yulian (Innovative: Journal Of Social Science Research, 2025)
The COVID-19 pandemic has given rise to a debate about who is the main actor in the policy-making process—whether the government bases policy on a democratic mandate or on a scientific-technocratic authority that is considered to be more “understanding” and has “knowledge” about the situation. This research aims to explore the extent to which the principles of epistocracy—power based on knowledge authority—play a role in the decision-making process during the pandemic. Using a qualitative approach and process tracing method, this article explores institutional and policy dynamics during the pandemic in Indonesia. Research findings indicate that the character of epistocracy in Indonesia's pandemic response is partial and temporary. This means that the epistocratic approach does not completely replace the democratic system during times of crisis and epistocracy only works during the pandemic period. Decisions with epistocratic nuances emerge gradually, rather than happening suddenly. Apart from that, deliberative processes also tend to be closed during the pandemic. Keyword: Epistocracy; Expert; Pandemic; Knowledge